Genetic and morphological analyses reveal a complex biogeographic pattern in the endemic barbel populations of the southern Italian peninsula. Issue 18 (29th August 2019) - Zaccara, Serena; Quadroni, Silvia; De Santis, Vanessa; Vanetti, Isabella; Carosi, Antonella; Britton, Robert; Lorenzoni, Massimo
Abstract: The Italian peninsula is a biodiversity hotspot, with its freshwater fish fauna characterized by high levels of local endemism. Two endemic fluvio‐lacustrine fishes of the genus Barbus (barbel, family Cyprinidae) have allopatric distributions in the Tyrrhenian and Adriatic basins of Italy. Barbus plebejus inhabits the mid‐ to northern Adriatic basins, while B. tyberinus is widespread in all central‐northern basins draining into the Tyrrhenian Sea. For basins in Southern Italy draining into the southern parts of these seas, there remains a knowledge gap on their barbel populations due to no previous genetic and morphological studies, despite their apparent biogeographic isolation. Correspondingly, this study quantified the presence and distribution of barbels in the Adriatic and Tyrrhenian basins of Southern Italy through genetic and morphological analyses of 197 fish sampled across eight populations. Testing of how local isolation has influenced the evolution and persistence of these populations was completed by examining sequence variation at two mitochondrial loci (cytochrome b and D‐loop) and performing geometric morphometric analyses of body shape, plus measuring 11 morphometric and meristic characters. Phylogenetic and morphological analyses revealed the presence of two genetically distinct lineages that differed significantly from adjacent B. tyberinus and B. plebejus populations. These two new taxa, here described as SI1 and SI2 Barbus lineages, are highly structured and reflect a complex mosaic biogeographic pattern that is strongly associated with the underlying hydrographical scenarios of the basins. The geographic isolation of these basins thus has high evolutionary importance that has to be considered for maintaining endemism. Abstract : In Southern Italy, apparent biogeographic isolation may have influenced barbel evolutionary structure. Through genetic and morphological analyses, we quantified the presence and distribution of barbels in Southern Italy describing two new taxa, highly structured and reflecting a complex mosaic biogeographic pattern that is strongly associated with the underlying hydrographical scenarios of the basins.